2018
DOI: 10.1080/02673843.2018.1528165
|View full text |Cite
|
Sign up to set email alerts
|

Youth strengths arise from the ashes of adversity

Abstract: With problem-oriented approaches to practice, policy and research, youth considered to be 'at-risk' are not often viewed from a strengths-based perspective. Explorations of youths' strengths are critical to help create environments where youth can flourish. The purpose of this research was to explore the resilience, healthy capabilities and strengths of youth at risk; from youth and staff perspectives across three community-based organizations in Western Canada. Through 17 interviews analyzed using hermeneutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Latent classes' transitions and their positive associations with the reduced number of actionable items were consistent with the study findings of youth strengths. Building strengths, a strength-based approach supports youth's personal recovery independent of improving youth mental health needs [24,42,43]. Results indicated that transitioning to a better group was associated with a lower number of actionable items at the end of an episode of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Latent classes' transitions and their positive associations with the reduced number of actionable items were consistent with the study findings of youth strengths. Building strengths, a strength-based approach supports youth's personal recovery independent of improving youth mental health needs [24,42,43]. Results indicated that transitioning to a better group was associated with a lower number of actionable items at the end of an episode of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The problem has been that youths' experiences have been evaluated against norms and practices set by adults (Iwasaki, 2016). Recently, the focus has shifted more toward strengths and assets (Lind et al , 2019). Positive youth development (PYD) theory and practice draw on positive psychology and emphasize youths' strengths, resources and opportunities (Larson, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Marginalized youths' strengths manifest themselves in many ways, such as trust and a positive attitude to opportunities (Ponciano, 2013) and also creativity, stubbornness and the acceptance of others (Nott and Vuchinich, 2016), loyalty, empathy, altruism and a willingness to influence (Lind et al , 2019) and a strong sense of purpose and willingness to overcome challenging situations (Sumner et al , 2018). Resilience is embedded in the PYD approach and understood not only as a personal capacity to overcome the negative effects of a harmful situation or experience but also as the capacity of a person's social circle to provide opportunities to young people who have been mistreated (Sanders et al , 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Concepts such as resiliency from psychology are also relevant. Lind et al (2019) using interpretive methods identified many strengths compiled from an analysis of interviews with youth resulting in an overarching metaphor “youth strengths arise from the ashes of adversity.” Some of the strongest themes within the interviews included the following: resilience, loyalty, altruistic, artistic, wanting to be included in decision making, perseverance, empathy, and creative. Spindle-Jackson and Collins (2021) argue that positive youth development approaches are particularly germane to workforce practice.…”
Section: Introductionmentioning
confidence: 99%